The Role Of Accounting In Optimizing Manufacturing Processes - Utepov Miyirman (Genius Journals, 2024)
Accounting plays a pivotal role in modern manufacturing processes, going beyond mere record-keeping to becoming a strategic enabler for decision-making, cost optimization, and process improvement. In a competitive global market, manufacturers face challenges such as increasing material costs, labor inefficiencies, and market demand fluctuations. Accounting provides the tools and methodologies to address these challenges by offering detailed insights into cost structures, profitability, and resource utilization. This article delves into the critical functions of accounting in manufacturing and examines how it can optimize processes to enhance overall productivity and profitability
Keywords: processes; profitability; challenges; structures